PENGARUH CONTENT MARKETING DAN CELEBRITY ENDORSER TERHADAP PURCHASE INTENTION DENGAN ATTITUDE SEBAGAI VARIABEL MEDIASI (Studi Pada Skincare Glad2Glow di Yogyakarta) - Alda Kaniza, Yosy; Cahya, Agus Dwi; Indraswari, Nurul Myristica (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the influence of content marketing and celebrity endorsers on purchase intention, with attitude as a mediating variable among Glad2Glow skincare consumers in Yogyakarta. A quantitative approach was applied, with 183 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that content marketing and celebrity endorsers have a positive and significant effect on both purchase intention and attitude, and that attitude has a positive and significant effect on purchase intention. Attitude also mediates the effect of content marketing and celebrity endorsers on purchase intention. Keywords: Content Marketing; Celebrity Endorser; Attitude; Purchase Intention; Glad2Glow